Inhibition of Lipid Peroxidation Induced by Ultraviolet Radiation by Crude Phlorotannis Isolated from Brown Algae Sargassum hystrix v. buxifolium C. Agardh - Agnes Nora Iska Harnita; Ign. Edi Santosa; Sudibyo Martono; Sudarsono Sudarsono; Sitarina Widyarini; Frans J.M. Harren (Universitas Gadjah Mada, 2013)
This study examines the antioxidant activity of crude phlorotannins from the brown algae Sargassum hystrix v. buxifolium (Chauvin) J. Agardh, through the inhibition of a lipid peroxidation reaction that is induced by the UV radiation. The antioxidant activity during the UV exposure was investigated using the laser-based photoacoustic method for the detection of the ethylene as indicator for lipid peroxidation. This involves an experiment that isolated crude phlorotannins from the ethyl acetate fraction of the Sargassum hystrix methanol extract, hereafter referred to as PFSH. It results in the antioxidant activity as a potent lipid peroxidation inhibitor. Statistically, such antioxidant activity is not significantly different than the commercial antioxidant, which is vitamin C (p > 0.05). The amount of the total phlorotannins, using the Folin-Ciocalteu method, was measured to be approximately 0.13% w/w. In addition, it is found that PFSH contains phlorotannins with low molecular weight (MW) (